Analysis of the linearity of the story on the creation of the game "Elephant Rescue.” - R.M Joko Priono; Sigit Winarso; Wilhelmus Filianto (Jurnal Indonesia Sosial Teknologi, 2024)
Media is an intermediary that can be used to convey information or messages in learning to achieve learning outcomes. Many types of media are used in the learning process. One of the media used in learning is games as educational media, called educational games. Educational games are games that are formed to hone thinking power, including increasing concentration and solving a problem. Educational stories based on local wisdom also serve to strengthen character education so that they can be well received without reducing the playing experience gained by players. Through the results of game testing, 40% of respondents strongly agreed that the understanding of conserving animals, especially elephants in Way Kambas Lampung National Park, was sought to be raised through the Elephant in Rescue Game, and 24% agreed that the understanding of conserving animals, especially elephants in Way Kambas Lampung National Park, was sought to be raised through the Elephant in Rescue Game. 60% of respondents agreed with the educational element presented in the game Elephant in Rescue, and 56% of respondents agreed that the application of the story in this game was appropriate. Based on the results of testing on respondents, it can be concluded that the application of stories and education about the importance of preserving animals, especially elephants in Way Kambas National Park, Lampung, can be conveyed well in accordance with what has been designed before.